Pengaruh Bauran Promosi, Pengetahuan Kesehatan Reproduksi Remaja Dan Peran Orang Tua Terhadap Pemanfaatan Pelayanan Kesehatan Peduli Remaja (PKPR) - Yulia Trisnawati; Sumihardi Sumihardi (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
Many adolescents engage in sexual behavior, which can be influenced by several factors including the promotion mix, adolescent reproductive health knowledge and the role of parents. The purpose of this study was to determine the effect of the promotion mix, knowledge of adolescent reproductive health and the role of parents on the utilization of Youth Care Health Services (PKPR) in Gema Nusantara Bukittinggi Health Vocational School in 2020. The sample of this study used purposive sampling, obtained as many as 84 respondents. The research instrument used a questionnaire. This type of research used in this research is quantitative research with cross sectional design. The results of multiple linear regression research variable promotion mix with a regression coefficient of 0.074 and a significance value of 0.001 means that there is a significant and positive influence on the promotion mix of utilization (PKPR), adolescent reproductive health knowledge variables with a regression coefficient of 0.357 and a significance value of 0.001 means there is a significant influence significant and positive knowledge of adolescent reproductive health on utilization (PKPR), the variable role of parents with a regression coefficient of 0.269 and the significance value of 0,000 means that there is a significant and positive influence on the role of parents on utilization (PKPR).